2012
DOI: 10.1002/jms.3080
|View full text |Cite
|
Sign up to set email alerts
|

Structures of oxaliplatin‐oligonucleotide adducts from DNA

Abstract: Oxaliplatin, [(1R,2R)-cyclohexane-1,2-diamine](ethanedioato-O,O')platinum(II) shows a great efficiency against colorectal cancer. Although the mode of action of oxaliplatin is not yet understood, it is commonly accepted that binding of oxaliplatin to DNA prevents DNA synthesis and alters protein to DNA binding. In order to elucidate the modified DNA-protein interaction and thus to understand the mechanisms leading to cellular misinterpretation of DNA information and apoptosis, we have identified the preferenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…It has previously been reported that oxaliplatin is involved in DNA damage by inducing DNA cross-links and activating the DDR (4,5). The present study demonstrated that MLN4924 and oxaliplatin treatment induced increased protein expression levels of p-H2A and p-CHK2 compared with single agent treatment in CRC cells.…”
Section: Mln4924 Increases the Oxaliplatin-induced Ddr And G2 Cell Cysupporting
confidence: 62%
See 2 more Smart Citations
“…It has previously been reported that oxaliplatin is involved in DNA damage by inducing DNA cross-links and activating the DDR (4,5). The present study demonstrated that MLN4924 and oxaliplatin treatment induced increased protein expression levels of p-H2A and p-CHK2 compared with single agent treatment in CRC cells.…”
Section: Mln4924 Increases the Oxaliplatin-induced Ddr And G2 Cell Cysupporting
confidence: 62%
“…Oxaliplatin (Sigma-Aldrich; Merck Millipore, Darmstadt, Germany) was dissolved in sterile water and stored at -20˚C. SW620 and HCT116 were seeded into 24-well plates at a density of 1x10 4 Western blotting. Cells were lysed with radioimmunoprecipitation assay lysis buffer (Beyotime Institute of Biotechnology, Haimen, China) containing phenylmethylsulfonyl fluoride (Beyotime Institute of Biotechnology), and lysates were centrifuged at 13,500 x g for 5 min at 4˚C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again the structure analysis of the modified oligonucleotides was based on ESI/MSMS data, but quantitative data were only accessible via LC/ICP‐MS . In this study we used phosphorus again to quantify DNA adducts in order to show DNA repair of cross links (Figure )…”
Section: Applicationsmentioning
confidence: 99%
“…Oxaliplatin induces apoptosis in CRC cells by damaging cellular DNA through the formation of intrastrand guanine-guanine and guanineadenine DNA links [12,13]. However, under the long-term use of oxaliplatin, cancer cells usually change their gene expression profile to acquire drug resistance against oxaliplatininduced apoptosis [14][15][16].…”
Section: Introductionmentioning
confidence: 99%